Clinical and Therapeutic Aspects of Envenomations Caused by Sponges and Jellyfish - Haddad, Vidal [UNESP]; Haddad, V; Tubaro, A.; Kim, E.; Kem, W. R.; Gopalakrishnakone, P. (Springer, 2016)
The injuries caused by aquatic animals have increased in recent decades due to the increase of human beings in these environments, especially for recreational activities. The highest percentages are associated with invertebrates such as sea urchins, jellyfish, and Portuguese man-of-war (echinoderms and cnidarians), but there are injuries caused by numerous other aquatic animals, including marine and freshwater sponges. In this review, the clinical, therapeutic, and preventive aspects of injuries and envenomation caused by sponges and cnidarians around the world are discussed.